The Role of Phase-Change Memory in Edge Computing and Analog In-Memory Computing: An Overview of Recent Research Contributions and Future Challenges - Alessio Antolini; Francesco Zavalloni; Andrea Lico; Said Quqa; Lorenzo Greco; Mauro Mangia; Fabio Pareschi; Marco Pasotti; Eleonora Franchi Scarselli (Sensors, 2025)
Phase Change Memory (PCM) has emerged as a promising non-volatile memory technology with significant applications in both edge computing and analog in-memory computing. This paper synthesizes recent research contributions on the use of PCM for smart sensing, structural health monitoring, neural network acceleration, and binary pattern matching. By examining key advancements, challenges, and potential future developments, this work provides a comprehensive state-of-the-art overview of PCM in these domains, highlighting the possible employments of PCM technology in further edge computing scenarios including medical and human body monitoring.